Command legacy a tactical primer for junior leaders - Millen, Raymond A. (Brassey's, 2002)
This title is a combat officer's conclusions about how to approach tactical problems and missions and about the links among tactical theory, doctrine and practice. It is designed to prime junior leaders for tactical operations, team building and professional development.